Pilot study shows skin-to-skin care with parents improves heart rate variability in preterm infants in the neonatal intensive care unit - Erin Swieter; Jessica M. Gross; Julia Stephen; Kristi Watterberg; Jessie R. Maxwell; Jessie R. Maxwell (Frontiers Media S.A., 2023)
BackgroundSkin-to-skin care in the newborn intensive care unit typically lasts for short periods of time and enhances breastfeeding, attachment, and parental self-esteem. Heart rate variability (HRV) increases with gestational age and is a measure of maturation of parasympathetic vs. sympathetic autonomic nervous system activity. HRV measurements may be useful in capturing changes in autonomic regulation in response to skin-to-skin care.ObjectiveTo analyze the effects of skin-to-skin care on HRV in preterm infants receiving respiratory support. We hypothesized that skin-to-skin care would result in a more mature pattern of parasympathetic activity.MethodsIn this prospective crossover study, infants <30 weeks' gestation and 1-6 weeks postnatal age had HRV recorded for 30 min before, during, and after skin-to-skin care sessions. HRV characteristics analyzed included the standard deviation of the normal-to-normal interval (SDNN), the root mean squared of successive differences of normal-to-normal intervals (RMSSD), and the standard deviation of decelerations (SDDec).Results10 infants between 25 5/7-29 6/7 weeks gestational age and 7-41 days postnatal age completed 22 sessions while receiving respiratory support (positive pressure ventilation or nasal cannula oxygen). Two measures of HRV (SDNN and RMSSD) were significantly decreased by the end of the skin-to-skin sessions, compared to pre-session values. SDNN decreased from a median of 10.44 ms before the session to 6.70 ms after being placed back in bed (p < 0.05), with RMSSD decreasing from a median of 6.80 ms before the session to 4.32 ms while being held at the end of 30 min (p < 0.05).DiscussionSkin-to-skin care with a parent resulted in a more mature autonomic nervous system pattern in preterm infants receiving respiratory support, suggesting physiologic benefit for the infant. No adverse events were seen during any session.